A 3D finite strain viscoelastic model with uncoupled structural and stress relaxations for shape memory polymers. (November 2021) - Wang, Yingyu; Zhu, Feilong; Rao, Qiong; Peng, Xiongqi
Abstract: In this paper, a 3D finite strain viscoelastic model with uncoupled structural and stress relaxations is proposed to characterize the thermomechanical behaviors of amorphous shape memory polymers (SMPs). The temperature- and rate-dependent viscoelastic behaviors and stress relaxation are described by the modified Eyring model and nonlinear Adam-Gibbs model based on molecular mechanism. A modified weight function analogous to frozen fraction in phase transition theory is proposed to further improve accuracy of the model. The developed model is implemented with MATLAB to simulate shape recovery experiments of amorphous SMPs under constraints or free in the literature. Good consistency between simulation results and experimental data is obtained. Highlights: Proposing a 3D finite strain viscoelastic constitutive model with uncoupled structural and stress relaxations for thermally induced shape memory polymers. Introducing a rate-dependent activation energy into nonlinear Adam-Gibbs model to make stress relaxation uncoupled with structural relaxation. Introducing a temperature-dependent activation energy to modified Eyring model. Developing a modified weight function used in Wang et al. (2021) to further improve model accuracy.